PROBLEMATIKA PEDAGANG BUAH KAKI LIMA DI KOTA PALANGKA RAYA - Hakim, Sofyan; Sali, Sali; Alfauji, Akhmad (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2018)
The problem of fruit street vendors is because they open their trade use the part of fruit street or sidewalk and other places for public